Tracer-Study: Identifikasi Masalah/Kendala Guru Bahasa Inggris SMA Dan SMK Kabupaten Kuala Kapuas Dalam Menulis Dan Mengimplementasikan Penelitian Tindakan Kelas - Nova, Susan Ira (FKIP, Universitas Palangka Raya, 2016)
This study investigates the internal and external problems facing by the English Teachers of Senior High School in Kuala Kapuas Regency to conduct Classroom Action Research (CAR). The data were gained through personal interview and Forum Group Discussion. The results of the study have revealed that the internal problems were unsufficient knowledge of CAR, low skill in composing scientific writing, teacher’s negative mind-set, and low control of self management. The external problems were unclear administrative stuffs, unfair chances to join the training and getting insignificant benefits of participating in a training, no information where to publish the result of CAR, and unsufficient facilities. To conclude, the respondents’ problems were mainly in unsufficient knowledge of CAR, low skill in composing a scientific writing, low control of self management, no strandard guideline for conducting and develoving CAR from the Regency Education Department, no training or guiding program about CAR, and no stimulus to conducting CAR.